Lack of seroresponse to SARS-CoV-2 booster vaccines given early post-transplant in patients primed pre-transplantation - Gleeson, Sarah; Martin, Paul; Thomson, Tina; Spensley, Katrina J.; Goodall, Dawn; Bedi, Rachna; Thind, Amarpreet Kaur; Seneschall, Charlotte; Gan, Jaslyn; McAdoo, Stephen; Lightstone, Liz; Kelleher, Peter; et al. (Frontiers in Immunology, 2023)
SARS-CoV-2 vaccines are recommended pre-transplantation, however, waning immunity and evolving variants mandate booster doses. Currently there no data to inform the optimal timing of booster doses post-transplant, in patients primed pre-transplant. We investigated serial serological samples in 204 transplant recipients who received 2 or 3 SARS-CoV-2 vaccines pre-transplant, with booster doses post-transplant. Spike protein antibody concentrations, [anti-S], were measured on the day of transplantation and following booster doses post-transplant. Infection episodes post-transplant are also described. In infection-naïve patients, post-booster [anti-S] did not change when V3 (1st booster) was given at 116(78-150) days post-transplant, falling from 122(32-574) to 111(34-682) BAU/ml, p=0.78. Similarly, in infection-experienced patients, [anti-S] on Day-0 and post-V3 were 1090(133-3667) and 2207(650-5618) BAU/ml respectively, p=0.26. In patients remaining infection-naïve, [anti-S] increased post-V4 (as 2nd booster) when given at 226(208-295) days post-transplant, rising from 97(34-1074) to 5134(229-5680) BAU/ml, p=0.0016. Whilst in patients who had 3 vaccines pre-transplant who received V4 as 1st booster, [anti-S] did not change, falling from 981(396-2666) to 871(242-2092) BAU/ml, p=0.62. Overall, infection pre-transplant and [anti-S] at the time of transplantation predicted post-transplant infection. As [anti-S] fail to respond to SARS-CoV-2 booster vaccines given early post-transplant, passive immunity may be beneficial to protect patients during this period.